2009
DOI: 10.1021/jp907711c
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Nanostructuring within Imidazolium Ionic Liquids: A Thermodynamic Study Using Photochromic Molecular Probes

Abstract: Following previous studies involving the thermal relaxation of spirocyclic compounds we extended our studies to investigate the formation of nano-structured domains in ionic liquids (ILs). Two compounds, spiropyran (BSP) and spirooxazine (SO) were added to imidazolium cation based ionic liquids with increasing chain lenghts (C 2 -C 12 ). Increasing side-chain length was found to have only minor effects on the rate of thermal relaxation of BSP and SO. BSP was found to be a suitable probe molecule as linear corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Nevertheless, the effect of nanostructuration/segregation of ionic liquids on the static and dynamic properties of these compounds has been established in previous works. 33,34,[36][37][38][39][40][41][42] A critical analysis of the enthalpies of vaporization for the [C N-1 C 1 im][NTf 2 ] ionic liquid series and the dependency of the data with the chain length of the alkyl group of the cation has been recently published. 35 Therefore, and considering the fact that literature data for this new ionic liquids are not available, in this work the discussion will be made focusing on the data obtained based on experimental vapor pressures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the effect of nanostructuration/segregation of ionic liquids on the static and dynamic properties of these compounds has been established in previous works. 33,34,[36][37][38][39][40][41][42] A critical analysis of the enthalpies of vaporization for the [C N-1 C 1 im][NTf 2 ] ionic liquid series and the dependency of the data with the chain length of the alkyl group of the cation has been recently published. 35 Therefore, and considering the fact that literature data for this new ionic liquids are not available, in this work the discussion will be made focusing on the data obtained based on experimental vapor pressures.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Despite the controversy around the so called trend shift on the enthalpies of vaporization, 35 the effect nanostructuration in ionic liquids was already detected in several other properties. 33,34,[36][37][38][39][40][41][42] This work presents vapor pressure data for the 1, )] spectrometer, and the solvent used was DMSO D6. The ionic liquids were found to be >99 wt.% purity.…”
Section: Introductionmentioning
confidence: 99%
“…26 The reason for this difference in trend is not clear at this point, but it may lie in the way the ions interact with the gel polymer chains, and the impact of these interactions on IL nano-domain structure. 27,28 In [P 6,6,6,14 (Figure 3a). As shown in Figure 4 and Figure S6).…”
Section: Swelling Rates Of the Disc Shaped Phosphonium Ionogelsmentioning
confidence: 99%
“…5 For example, a recent report has shown that surfactant–ionic‐liquid‐based microemulsions can be used to produce polymer nanoparticles, gels, and open‐cell porous materials 8g. In the work presented here, we utilized 1‐butyl‐3‐methylimidazolium tetrafluoroborate ([bmim][BF 4 ], Scheme ) as the polar phase for microemulsions; this system is known to form organized structures in the presence of additives12 Researchers have demonstrated nanosized reverse micelles dispersed with Triton X‐100 (TX‐100) in cyclohexane by using [bmim][BF 4 ] 8a. c–e, k, m, p,q Dynamic light scattering (DLS) confirmed that the RTIL microemulsions contained nanosized structures,8p,q and similar to “classic” water‐in‐oil (w/o) microemulsions, the droplet volume of these nanosystems increase regularly as micelles were progressively swollen with added [bmim][BF 4 ] 8m.…”
Section: Introductionmentioning
confidence: 99%